2017
DOI: 10.1111/bjd.15778
|View full text |Cite
|
Sign up to set email alerts
|

Hidradenitis suppurativa and electrocardiographic changes: a cross‐sectional population study

Abstract: SummaryBackground Hidradenitis suppurativa (HS) is a chronic, inflammatory skin disease, recently associated with metabolic syndrome, subclinical atherosclerosis and increased risk of cardiovascular disease. Objectives To investigate the hitherto unknown electrocardiographic (ECG) changes associated with HS, which have recently been associated with significant cardiovascular burden. Methods Data were obtained from the cross-sectional Danish General Population Study (GESUS). HS diagnosis was based on a validate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…The risk of cardiovascular or cerebrovascular death was also significantly higher for the patients with HS. These data were comparable with previous studies …”
Section: Scientific Session 1: Epidemiology and Burden Of Diseasesupporting
confidence: 93%
“…The risk of cardiovascular or cerebrovascular death was also significantly higher for the patients with HS. These data were comparable with previous studies …”
Section: Scientific Session 1: Epidemiology and Burden Of Diseasesupporting
confidence: 93%
“…Reduced quality of life, social isolation [28,29] Sexual dysfunction [31] Depression, anxiety, schizophrenia [29,34,35] Increased antidepressant drug use [36] Increased suicide risk [36] Development of strategies to recognize and treat those psychiatric comorbidities in patients with HS is warranted Older patients, smokers, and patients with depression may benefit from periodic screening for long-term opioid use HS hidradenitis suppurativa, CD Crohn's disease of subclinical atherosclerosis [14]. In a crosssectional Danish general population study, mean resting heart rate in patients with severe HS was significantly higher compared with controls [15]. A population-based cohort study using individual-level linkage of nationwide administrative registers indicated that HS was associated with a significantly increased risk of adverse CV outcomes and all-cause mortality independent of measured confounders [16].…”
Section: Comorbiditiesmentioning
confidence: 99%
“…This is a crucial step in ensuring high data accuracy compared with data obtained by online or postal surveys. The only limitation of the present study is that the authors chose to use a generic questionnaire (Skindex-29) rather than a vitiligo-specific questionnaire such as the Vitiligo Impact Patient scale 3 or the VITIQoL, 4 which reflect better patient expectations and have the advantage of covering all aspects of the burden of vitiligo in daily life. To conclude, the study by Bae et al 2 is an important step towards confirming the impact of vitiligo on patient QoL.…”
Section: A D C O H E Nmentioning
confidence: 99%
“…It is not uncommon that patients are pessimistic about disease progression, treatment efficacy and their future health. 4,5 Nevertheless, the findings of Hjalte et al suggest that thanks to biologics, patients have been placed on a whole new trajectory regarding disease course and HRQoL. 3 The sustained improvement in HRQoL has been observed by using both a dermatology-specific (DLQI) and a generic (EQ-5D) measure.…”
mentioning
confidence: 99%